Can incubators work in Africa? Acorn Technologies and the entrepreneur-centric model - Singer Peter A; Masum Hassan; Chakma Justin (BMC, 2010)
Abstract Background Incubators are organizations that support the growth of new and typically technology-based enterprises, by providing business support services that bring together human and financial capital. Although the traditional role of incubators has been for economic development, they may also be a useful policy lever to tackle global health, by fostering the development and delivery of local health innovation. Given its high disease burden, life sciences incubators hold particular potential for Africa. As the most industrially advanced African nation, South Africa serves as a litmus test for identifying effective incubator policies. The case study method was used to illustrate how one such publicly funded incubator founded in 2002, Acorn Technologies, helped to catalyze local health product innovation. Discussion Acorn helped to support twelve biomedical device firms. One of them, Real World Diagnostics, was founded by a trainee from Acorn's innovative internship program (Hellfire). It developed rapid strip diagnostic tests for locally prevalent diseases including schistosomiasis and HIV, and reported $2 million (USD) in revenue in 2009. Acorn achieved this success by operating as a non-profit virtual incubator with little physical infrastructure. Employing a virtual model in combination with stringent selection criteria of capital efficiency for clients proved to be effective in reducing its own fixed costs. Acorn focused on entrepreneurship training and networking, both critical at an early stage in an environment dominated by multinational biomedical device companies. Acorn and its clients learned that employing a cross-subsidy business model allowed one to generate royalty revenue through imports to subsidize R&D for local diseases. However, funding constraints and government expectations for rapid self-sustainability forced Acorn to merge with its sister biotechnology incubator in 2009. Summary A key to Acorn's achievements was identifying entrepreneurs with technologies with health and economic impact, and providing them with flexible support from an early stage. A virtual organizational model helped Acorn to focus on supporting entrepreneurs. Governments and funders may wish to consider incubation strategies that draw from these good practices. With the right policies and business models, incubators have the potential to generate both health and economic benefits for Africa.